To solve the expression \( 12^{-5} \cdot 12^7 \) using the Product Rule of Integer Exponents, we can apply the rule which states that when multiplying two powers with the same base, we add the exponents:
\[ a^m \cdot a^n = a^{m+n} \]
In this case, \( a = 12 \), \( m = -5 \), and \( n = 7 \). Applying the Product Rule:
\[ 12^{-5} \cdot 12^7 = 12^{-5 + 7} = 12^{2} \]
Now, we need to simplify \( 12^{2} \):
\[ 12^{2} = 12 \times 12 = 144 \]
Thus, the equivalent expression for \( 12^{-5} \cdot 12^7 \) is \( 12^2 \), which evaluates to:
\[ \boxed{144} \]
So the final answer, without exponents, is \( 144 \).